MEDICATION ADHERENCE, SELF-MOTIVATION, AND FAMILY PERSPECTIVES: A QUALITATIVE STUDY ON PATIENTS WITH TYPE 2 DIABETES MELLITUS CHALLENGES - Ahmad, Verousson; Issaray, Disa Yuni Shabrina; Nilta Manzila; Kayla Amabel Lavina Pieter; Imanuel Yuerrico Subianto; Ahmad Azhar Marzuqi; Sri Soenarti; Aulia Rahmi Pawestri (Majalah Kesehatan, 2026)
Type 2 diabetes mellitus (T2DM) is a chronic illness that must be effectively managed to prevent complications. Medication adherence, self-motivation, and family support all influence the success of disease management. This qualitative study explored T2DM patients' experiences of medication adherence, self-motivation, and family perspectives on illness management. Data were collected through in-depth interviews with ten purposefully selected T2DM patients. Data analysis was conducted using the Colaizzi    method to identify emerging themes. The study found varying levels of medication adherence, with some patients strictly following medical instructions, while others were inconsistent due to boredom or a fear of medication side effects. Both intrinsic and extrinsic motivations play crucial roles in patient self-management. Family support, both emotional and instrumental, is crucial in helping patients maintain their medication routine and stabilize blood glucose levels. Medication adherence, self-motivation, and family support all play a crucial role in achieving successful diabetes control. Interventions that increase patient motivation and strengthen family support can enhance adherence and improve health outcomes in patients with T2DM.